(untitled) - Tolkien, J. R. R. (Boston, 2002)
A work of immense narrative power that can sweep the reader up and hold him enthralled for days and weeks
Keywords: Baggins, Frodo (Fictitious character),Middle Earth (Imaginary place); Fiction,Fiction